National guidelines for haemopoietic stem cell therapy (Kementerian Kesihatan Malaysia, 2009)
"This current edition of the National Guidelines for Haemopoietic Stem Cell Therapy stipulates the required standards for any clinical facility in Malaysia performing haemopoietic stem cell transplants." -- Foreword